FACE TO FACE. - ADLER, JERRY (Smithsonian, 2015)
The article discusses the use of computers in researching the human face and facial expressions, heavily referencing the engineer and start-up business co-founder Rana el Kaliouby. An overview of el Kaliouby's start up company Affectiva's role in designing software to interpret facial expressions is provided.